2021
DOI: 10.3168/jds.2020-19072
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility, lactation performance, plasma metabolites, ruminal fermentation, and bacterial communities in Holstein cows fed a fermented corn gluten-wheat bran mixture as a substitute for soybean meal

Abstract: The purpose of this research was to investigate the effects of replacing soybean meal (SBM) with a fermented corn gluten-wheat bran mixture (FCWM) on nutrient digestibility, lactation performance, plasma metabolites, ruminal fermentation, and bacterial communities in Holstein cows. Nine healthy multiparous (parity = 3) Holstein cows with similar body weights (624 ± 14.4 kg), days in milk (112 ± 4.2), and milk yields (31.8 ± 1.73 kg; all mean ± standard deviation) were used in a replicated 3 × 3 Latin square de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 57 publications
4
4
0
Order By: Relevance
“…In this study, rumen pH did not change with increasing IHEEB and CWH replacement which was similar to the results of Jiang et al ( 32 ). Rumen fluid ammonia-N concentration is related to the degradation of dietary protein in the rumen, which is utilized by rumen microorganisms.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, rumen pH did not change with increasing IHEEB and CWH replacement which was similar to the results of Jiang et al ( 32 ). Rumen fluid ammonia-N concentration is related to the degradation of dietary protein in the rumen, which is utilized by rumen microorganisms.…”
Section: Discussionsupporting
confidence: 92%
“…The DNA was extracted from the samples using an MN NucleoSpin 96 Soi DNA kit (Gene Company Limited) according to the kit's instructions. The DNA obtained from each sample was subjected to 2-step PCR amplification to construct a small-fragment sequencing library described by Jiang et al ( 32 ). The PCR products obtained in the first step of amplification were used as templates for the second step of Solexa PCR amplification (Applied Biosystems Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the previous study (Jiang et al 2021 ), our results found that the rumen dominant bacteria phyla were Bacteroidetes and Firmicutes , regardless of dietary treatments. However, the third dominant bacterium in this study was Cyanobacteria , rather than Proteobacteria, as reported in many studies.…”
Section: Discussionsupporting
confidence: 93%
“…Several other core members present in all treatment groups are beneficial to both growth parameters and pathogen control. One genus conserved across all groups was Bacteriodes, which is positively associated with the intestinal IgA response in broilers by enhancing the expression of several genes involved in the IgA response [65]. Specifically, B. fragilis has been identified as beneficial to gastrointestinal health through succinic and acetic acid production and has been considered in human health as a probiotic to combat intestinal inflammation [63,64].…”
Section: Plos Onementioning
confidence: 99%